Evaluating the impact of drying on leaching from a solidified/stabilized waste using a monolithic diffusion model - Chen, Zhiliang; Zhang, Peng; Brown, Kevin G.; van der Sloot, Hans A.; Meeussen, Johannes C.L.; Garrabrants, Andrew C.; Delapp, Rossane C.; Um, Wooyong; Kosson, David S. (Waste management (Elmsford), 2023)
[Display omitted] •A monolithic diffusion model was used to estimate the leaching from Cast Stone.•Physical retention of constituents by monoliths was reduced by drying.•Leaching of major and redox-sensitive constituents was evaluated.•Drying waste forms increased the subsequent release fluxes of Cr and Tc. The release rates of constituents of potential concern from solidified/stabilized cementitious waste forms are potentially impacted by drying, which, however, is not well understood. This study aimed to identify the impacts of drying on subsequent leaching from Cast Stone as an example of a solidified cementitious waste form. The release fluxes of constituents from monoliths after aging under 100, 68, 40, and 15 % relative humidity for 16, 32, and 48 weeks, respectively, were derived from mass transfer tank leaching tests following EPA Method 1315. A monolithic diffusion model was calibrated based on the leaching test results to simulate the leaching of major and redox-sensitive constituents from monoliths after drying. The reduction in physical retention of constituents (tortuosity-factor) in the unsaturated zone was identified as the primary impact from drying on subsequent leaching. Fluxes of both major (i.e., OH–, Na, K, Ca, Si, and Al) and redox-sensitive constituents (i.e., Tc, Cr, Fe, and S) from monoliths during leaching were well described by the model. The drying-induced reduction of tortuosity-factor and concomitant changes in porewater pH and redox conditions can significantly change the subsequent release fluxes of pH- and redox- sensitive constituents.